Electromagnetic dipolar modes in magnetized nonuniform plasma-vacuum-metal waveguide - Azarenkov, N.A.; Olefir, V.P.; Sporov, A.E. (Problems of Atomic Science and Technology, 2023)
This article presents the results of theoretical study of the phase and attenuation properties of the dipolar electromagnetic modes in cylindrical plasma-vacuum-metal waveguide structure. Plasma is described in hydrodynamic approach and is supposed to be slightly non-uniform in axial direction and strongly non-uniform in radial direction. It was studied the influence of the external magnetic field value, the electron effective collision frequency and other waveguide parameters on the phase and attenuation properties of the considered waves. Наведено результати теоретичних досліджень фазових властивостей та просторового загасання дипольних електромагнітних хвиль, що поширюються в циліндричній хвилеводній структурі плазма – вакуум – метал. Плазма розглядається в гідродинамічному наближенні та вважається слабко неоднорідною в аксіальному напрямку та сильно неоднорідною в радіальному напрямку. Досліджено вплив величини зовнішнього магнітного поля, ефективної частоти зіткнень електронів та інших параметрів хвилеводної структури на фазові властивості та просторове загасання дипольних хвиль.